Prevalence and Predictors of YouTube Use among Undergraduate Medical Students: A Cross Sectional Study from a Medical School of Riyadh, Saudi Arabia - Saleh Aldobekhi, Faris Suleiman (Bangladesh Journal of Medical Science, 2024)
Introduction: The use of YouTube has increased now among medical students to revise the curricular content, to better understand them and also to share ideas. This study was carried out to find out the prevalence and predictors of use of YouTube by medical students. Methodology: A cross-sectional study was carried out to assess the prevalence and predictors of use of YouTube as an extracurricular way of enhancing learning experience among medical students of Saudi Arabia for a period of 06 months from February 2023 to July 2023. A pre-validated self-administrated questionnaire consisting of the following sections like sociodemographic details, the predictors for the use of YouTube videos which consisted of frequency of use, grading of its usefulness etc. was used for data collection. Templates were generated in MS Excel sheet and analysis of data was done using SPSS software version 22. Quantitative variables were presented as frequency and percentages while chi square test of significance was used to demonstrate the associated between categorical variables. The value of significance was set as p less than 0.05. Results: The prevalence of use YouTube was 94.1% among medical students in a medical school of Saudi Arabia, out of which 73.8% use it for both educational and entertainment purpose and about 71% of them find it very useful for educational purpose. About 43.7% of students use directed search strategy and most opined that it helped in better understanding. Most students use YouTube for upto one hour. Male students of age group 20 – 22 years were more involved in using YouTube videos as compared to female students or of other age groups and this association was statistically significant. Conclusion: YouTube use is highly prevalent among medical students to better understand the subject matter and to revise them. Male students use them more often as compared to female students. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S122-S126